MENGHADIRI PERAYAAN HARI BESAR AGAMA NON ISLAM PERSPEKTIF AL-QUR’AN - Faldiansyah, Iqrom (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M) IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2019)
In the context of attending the commemoration of other religions' holidays in the view of the Qur'an, there are almost no verses that specifically discuss the issue of